Odpowiedź:
Szczegółowe wyjaśnienie:
Zad.1.
[tex](-1)^{2} - 5 = - 4 *(-1) = 1 - 5= 4*(-1) = - 4 = -4 \\0^{2} - 5 = -4 * 0 = 0 - 5 = -4*0 = - 5 = 0 \\2^{2} - 5 = -4 *2 = 4 - 5 = 4 * 2 = -1 = 8[/tex]
Odpowiedź: (-1)
Zad.2.
a) 3x - 5 = 4 + 2x
3x - 2x = 4 + 5
x = 9
b) 3(-2x + 5 ) = -( 7x + 5 )
-6x + 15 = - 7x - 5
-6x +7x = -5 - 15
x = - 20
c) x - ( 7 + 2x ) = 2( x - 1 ) + 1
x -7 - 2x = 2x - 2 + 1
x - 2x - 2x = -2 +1 + 7
- 5x = 6 |: -5
x = - [tex]\frac{6}{5}[/tex] = -1 [tex]\frac{1}{5}[/tex]
nie do końca mam pewność czy dobrze bo miałam to dosyć dawno ale myślę, że pomogłam. :)